Nerve growth factor inhibits sympathetic neurons’ response to an injury cytokine - Shadiack, Annette M. (The National Academy of Sciences, 1998)
Axonal damage to adult peripheral neurons causes changes in neuronal gene expression. For example, axotomized sympathetic, sensory, and motor neurons begin to express galanin mRNA and protein, and recent evidence suggests that galanin plays a role in peripheral nerve regeneration. Previous studies in sympathetic and sensory neurons have established that galanin expression is triggered by two consequences of nerve transection: the induction of leukemia inhibitory factor (LIF) and the reduction in the availability of the target-derived factor, nerve growth factor. It is shown in the present study that no stimulation of galanin expression occurs following direct application of LIF to intact neurons in the superior cervical sympathetic ganglion. Injection of animals with an antiserum to nerve growth factor concomitant with the application of LIF, on the other hand, does stimulate galanin expression. The data suggest that the response of neurons to an injury factor, LIF, is affected by whether the neurons still receive trophic signals from their targets.